Cisco IOS Access Lists - Sedayao, Jeff (O'Reilly, 2011)
Cisco routers are used widely both on the Internet and in corporate intranets. At the same time, the Cisco Internet Operating System (IOS) has grown to be very large and complex, and Cisco documentation fills several volumes.